"Trzej mocarze, swobodom spokojnego kraju zawisni..." Obrazy konfederacji barskiej i pierwszego rozbioru w poezji Adama Naruszewicza - Przekora, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
Adam Naruszewicz - the court poet of the last king of Poland was born on 20th October 1733 in Polesie. He studied at Villinus University and in Lyon. Thanks to Adam Kazimierz Czartoryski he established a very close friendship with Stanisław August Poniatowski. In the course of time he started to bring out his political opinions and put some of his plans into practice. He edited Zabawy Przyjemne i Pożyteczne - the first Polish literary magazine. Franciszek Bohomolec printed his main works in Dzieła. However, the first publications has already been issued in Zabawy Przyjemne i Pożyteczne. As far as literary writing is concerned, Adam Naruszewicz gave his undivided attention to contemporary situation. It was difficulties in the country and on the King’s court that inspired Naruszewicz to express his opinions in public. The resources of contemporary political situation, particularly the times of Barski Confederation, the First Partition of Poland and the dissolution of Delegation Representatives were found between 1768—1775 in Poniatowski’s royal collection. The above events, in Adam Naruszewicz’s poems, are presented in the following order: The Barski and Radom Confederation, the abduction of the King and the Frist Partition of Poland. The plots are very important in poet’s life. The writer perceives and comments on the subject touching various areas. Above all, patriotism and love to the Country are the most important issues in Naruszewicz’s works.